2018
DOI: 10.3847/2041-8213/aae3e2
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Resolves the Stellar Birth Explosion in Distant Quasar 3C298

Abstract: Galaxies are believed to experience star formation and black hole driven nuclear activity symbiotically. The symbiosis may be more extreme in the distant universe, as far-infrared photometry with the Herschel Space Observatory has found many cases of ultraluminous cool dust emission in z>1 radio galaxies and quasars, which could have its origin in the central black hole activity, or in extreme starbursts. We here present strong evidence for an extreme circumnuclear starburst in the z=1.439 quasar 3C298. Our un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Interestingly, for 3C 298 and 3C 318, where both high spatial resolution imaging of the dust and Hα emission are present, there is a significant misalignment between the maps. In places where we see evidence for recent star formation based on nebular emission-line ratios in 3C 298 and 3C 318, Barthel et al (2018) and Barthel & Versteeg (2019) do not see any dust emission. For the case of 3C 298 in the location where we see recent star formation traced by Hα, we also detect a molecular reservoir; however, no dust emission is present there.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, for 3C 298 and 3C 318, where both high spatial resolution imaging of the dust and Hα emission are present, there is a significant misalignment between the maps. In places where we see evidence for recent star formation based on nebular emission-line ratios in 3C 298 and 3C 318, Barthel et al (2018) and Barthel & Versteeg (2019) do not see any dust emission. For the case of 3C 298 in the location where we see recent star formation traced by Hα, we also detect a molecular reservoir; however, no dust emission is present there.…”
Section: Discussionmentioning
confidence: 60%
“…We therefore believe that the AGN is responsible for driving the majority of the observed outflows within our sample. Barthel et al (2017Barthel et al ( , 2018; Barthel & Versteeg (2019) explores a sample of radio-loud quasars that include several objects from our sample (4C09.17, 3C 298, 4C04.81, and 4C05.84). They find a tentative correlation between the SFR and the equivalent width of the CIV λλ 1548 Å, 1550 Å absorption lines.…”
Section: Sourcementioning
confidence: 99%
“…We therefore believe that the AGN is responsible for driving the majority of the observed outflows within our sample. Barthel et al (2017Barthel et al ( , 2018 and Barthel & Versteeg (2019) explore a sample of radio-loud quasars that include several objects from our sample (4C09.17, 3C298, 4C04.81, and 4C05.84). They find a tentative correlation between the SFR and the equivalent width of the CIV λλ 1548 Å, 1550 Å absorption lines.…”
Section: Driving Source Of the Ionized Outflowsmentioning
confidence: 99%
“…For example, from Figure 7, an Arp 220 SED with slightly more synchrotron emission would appear as a dipping source in the SPT-SZ bands. In addition, multiwavelength follow-up observations of powerful radio galaxies and steep radio-spectrum quasars have shown these sources can have spectra that dip at roughly 1 mm (Haas et al 2006), with contributions to the emission at far-IR and submillimeter wavelengths expected to be caused by dust heating from the AGN and star formation, and observations with Herschel have shown that a substantial fraction of these sources may be radio-loud ULIRGs (Podigachoski et al 2016;Barthel et al 2018). As mentioned in Section 4.10, follow-up observations at 870 μm with LABOCA of a set of 21 sources with dipping spectra in the SPT bands have indicated that while a few have fluxes at 870 μm consistent with the presence of dust, most of these sources have fluxes at 870 μm that are too low to be consistent with a DSFG spectrum.…”
Section: Dusty Sourcesmentioning
confidence: 99%